2014
DOI: 10.1177/0194599814542590
|View full text |Cite
|
Sign up to set email alerts
|

The Cost and Inpatient Burden of Treating Mandible Fractures: A Nationwide Inpatient Sample Database Analysis

Abstract: The average cost for treatment of mandible fractures was $35,804 per person with increased expenditures for older patients and those with a history of mental illness, cardiovascular disease, or substance abuse. To improve outcomes and reduce hospital charges, outpatient resources and inpatient protocols should be implemented to address the factors we identified as contributing to higher costs and increased hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
1
30
1
1
Order By: Relevance
“…The mean length of hospital stay for a mandible fracture is 2.65 days, and the mean hospitalization cost is $35 804. 13 Since the first commercially successful bicycle helmet, a polystyrene-lined hard shell, was released in 1975, most bicycle helmet designs have not added significant protection of the face. 14 Currently, the Consumer Product Safety Commission determines bicycle helmet standards in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The mean length of hospital stay for a mandible fracture is 2.65 days, and the mean hospitalization cost is $35 804. 13 Since the first commercially successful bicycle helmet, a polystyrene-lined hard shell, was released in 1975, most bicycle helmet designs have not added significant protection of the face. 14 Currently, the Consumer Product Safety Commission determines bicycle helmet standards in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding medical costs, a cross-sectional study using the 2009 NIS database and 1481 patients with isolated mandibular fractures [5] reported that the average per-patient treatment cost was $35,804, and that patients with a history of mental illness, cardiovascular disease, increased age, and substance abuse had higher costs; most patients with an isolated mandibular fracture requiring treatment were uninsured (47%) males with lower socioeconomic status; the incidence of alcohol abuse was 12% and mental illness incidence was 5.5%. The average hospital stay of alcoholics was 1 day longer, and their medical costs were $10,000 more than those of nonalcoholics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the NIS is based on ICD-9 codes, the complication rate may have been underestimated. [5] Furthermore, Pena et al [5] pointed out that motor vehicle accidents and sports injuries have a higher likelihood of causing poly-trauma injuries, and an isolated mandibular trauma is most likely the result of an assault. Therefore, because the present study excluded polytrauma, a higher proportion of injuries resulting from assaults may have been included versus other causes of mandibular fractures.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…fratura de mandíbula corresponde a $35.804 o que pode constituir-se em um grande problema de saúde pública [24]. Christensen et al conduziram um estudo retrospectivo de 3 anos em um hospital escola em New Orleans (USA) para identificar fatores de risco para o desenvolvimento de complicações maiores após redução aberta e fixação interna de fraturas de mandíbula.…”
unclassified